The Importance of Domestic Tourism Education in Tthe COVIC-19 Pandemic - Zouy Lie; Liang Boen (International Journal of Instruction and Smart Education, 2023)
In 2020, the world faced a new challenge. The coronavirus, which in a few days turned into a pandemic, completely changed human consciousness and lifestyle. The pandemic also affected the tourism sector, which led to some changes. In the conditions of the pandemic, the borders in China were closed, as a result of which Chinese citizens were restricted from traveling abroad. The closure of the borders prompted the development of domestic tourism in China. Most popular became Tourism trips to the mountainous regions. The article examines the features of the growth of tourist flows on the example of Guilin as a result of restrictions during a pandemic. After the spread of the COVID-19, domestic tourism has become the most interesting and developing direction of tourism. I would like to point out that the development of domestic tourism is especially important for the development of peripheral regions, where lower-income people live compared to other large regions, whose living conditions are quite harsh, they have to solve quite severe problems at the beginning of each tourist season. This article clearly discusses the problem of low education, which hinders the development of domestic tourism in China and the growth of economic income of the population living in tourist areas.